The Influence Of Compensation and Work-Life Balance On Employee Performance at Suweger Indonesia In Surabaya City - Muhammad Saifuddin Fajari; Sulastri Irbayuni (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study examines the influence of work-life balance and compensation on employee performance, focusing on 50 part-time student employees at Suweger Indonesia in Surabaya. Respondents were selected through purposive sampling, targeting individuals balancing academic and work responsibilities. The analysis utilized the Partial Least Square (PLS) method and revealed that compensation significantly and positively influences employee performance, indicating that improved compensation boosts performance. Meanwhile, work-life balance shows a positive but statistically insignificant effect. These results highlight the dominant role of compensation in improving employee performance, complemented by the contribution of work-life balance.